PREPARING FUTURE INFORMATICS TEACHERS FOR PEDAGOGICAL ACTIVITY IN THE PROCESS OF EDUCATIONAL PRACTICE AS AN IMPORTANT PEDAGOGICAL PROBLEM - H. Q. Mahkamov (Galaxy International Interdisciplinary Research Journal, 2022)
Determining the content and levels of improving the structural and functional model of methodological training by justifying the main directions of training students of pedagogical higher educational institutes for professional activity provides pedagogical opportunities for preparing them for professional-pedagogical activity. In our study, improvement of innovative technologies of professional and pedagogical activity of future information teachers, achieving a positive result through emotional-valuable attitude is interpreted as a type of activity.